2013
DOI: 10.1673/031.013.11101
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Element ‘roo’ Attaches to Nuclear Matrix of theDrosophila melanogaster

Abstract: The genome of eukaryotes is organized into structural units of chromatin loops. This higher order organization is supported by a nuclear skeleton called the nuclear matrix. The genomic DNA associated with the nuclear matrix is called the matrix associated region (MAR). Only a few genome-wide screens have been attempted, although many studies have characterized locusspecific MAR DNA sequences. In this study, a MAR DNA library was prepared from the Drosophila melanogaster Meigen (Diptera: Drosophilidae) genome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We identified TFBSs using the JASPAR database (see Material and Methods ). We also specifically looked for conservation of the regulatory regions previously described in the roo family [ 8 , 30 ], and for conserved core promoter motifs [ 1 ] ( Fig 3A and S2A Table ). Overall, there was very little diversity among the nine solo-LTRs ( S3A Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified TFBSs using the JASPAR database (see Material and Methods ). We also specifically looked for conservation of the regulatory regions previously described in the roo family [ 8 , 30 ], and for conserved core promoter motifs [ 1 ] ( Fig 3A and S2A Table ). Overall, there was very little diversity among the nine solo-LTRs ( S3A Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…These roo elements differ in the insertion site and in their orientation. On the other hand, all elements have the same size and show high sequence conservation: all cis-regulatory elements previously described in roo LTRs are highly conserved [ 8 , 30 ]. We further investigated whether these different insertions were functionally equivalent by performing 5’-RACE, gene expression, and phenotypic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Early research demonstrated that active transposons exist in germline cells (Bucheton, 1990). Transposons can move in the genome by insertion and transcription and thus interrupt the normal expression of genes (Kazazian, 2004;Mamillapalli et al, 2013). The main function of piRNA is the silencing of transposable elements (Senti and Brennecke, 2010;Weick and Miska, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the same gypsy sub-sequence that contains the insulator/silencer function (described above), also functions as MAR/SAR (matrix attachment region/scaffold attachment region), connecting a transcriptional role to a structural role of the gypsy retrotransposon [69]. A sequence displaying MAR function was also identified and characterized in the roo element [70]. Although this aspect is not deeply investigated, these results highlight a cis-structural role of TEs, whose importance is comparable to the role of TEs in centromeres and telomeres.…”
Section: Structural Role Of Cis-operating Sequences Within Tesmentioning
confidence: 99%